Dinamika dan Fondasi Pendidikan Islam pada Masa Khilafah Rashidah - Wahyudi, Ardi; Pratama, Randika; Purwadi, Ario (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2025)
This study explores the dynamics of Islamic education during the era of the Khulafāʾ al-Rāshidīn, the main objective of this research is to uncover the educational methods, institutions, and policies implemented by the caliphs, as well as their contributions to the dissemination of Islamic knowledge. This research employs a library research method as its primary approach. The findings indicate that although education during this period had not yet been formally institutionalized, it had already established a solid system and foundational values. The halaqah, talaqqi, and lecture methods served as the primary models of instruction, while mosques and kuttabs functioned as the main centers of learning. Umar ibn Khattab actively promoted education by sending companions as teachers to newly integrated Islamic regions and emphasizing the importance of mastering the Arabic language and religious sciences. These findings affirm that the era of the Khulafāʾ al-Rāshidīn laid the foundational framework for an inclusive, character-building, and socially integrated Islamic education system.